Valuation of Environmental Services City Park 1 BSD Using the Travel Cost Method (TCM) and Willingness To Pay (WTP) - Munawir, Abdillah; Armawan, Andre; Nurhasanah, Nurhasanah (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
BSD City Park 1 has quite complete functions, including ecological, social, and aesthetics, as well as is also a city landmark and a cheap and healthy tourist attraction for residents, including visitors from outside BSD City. The study aimed to find the factors that influence the number of public visits to City Parks and to determine the value of environmental services from City Park 1 BSD through a revealed preference approach using the Individual Travel Cost Method (ITCM) and Willingness To Pay (WTP). Economic valuation through revealed preference using the Travel Cost Method (TCM) calculation, the individual Consumer Surplus value is IDR 55,664/visit with an average stay of 4.8 personal holidays per year. If it is estimated that there are 104,150 visits/year, the Economic Value of City Park 1 BSD is estimated at IDR 5,797,422,757/year. The Willingness to Pay (stated preference) analysis results for additional facilities include the average individual WTP for other sports facilities of IDR 7,619.00; The average particular WTP for adding the number of trash cans is Rp.7,619.00; The average individual WTP increases the number of toilets by IDR 15,000.00.